REPLANTASI GIGI INSISIF SENTRAL ATAS PADA ANAK USIA 3½ TAHUN (LAPORAN KASUS) - Ike Siti Indiarti; Sri Harsini; Sarworini Bagio Budiardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
Traumatic usually in children because falls and the treatment is moderate. Frequency of traumatic is 7 - 13% from all traumatic case in primary dentition. Avulsion is one of it and the treatment is replantation. This treatment needs an accurate examination. The function of primary dentition is for bite, talk, and esthetics especially for the children in the growth and development stage. In this case the patient is a girl, 3½ years od, with incisive ventral upper jaw avulsion because of falls, replantation is the choice treatment, replantation can be dpne 4 hours after falls. The clinical result after 5 month is no luxation, and the radiographic interpretation is good bone healing in incisive central.